Microinvasive Glaucoma Stent (MIGS) Surgery With Concomitant Phakoemulsification Cataract Extraction: Outcomes and the Learning Curve. Issue 7 (July 2017) - Al-Mugheiry, Toby S.; Cate, Heidi; Clark, Allan; Broadway, David C.
Abstract : Purpose: To evaluate learning effects with respect to outcomes of a microinvasive glaucoma stent (MIGS) inserted during cataract surgery in glaucoma patients. Patients and Methods: Single surgeon, observational cohort study of 25 consecutive Ivantis Hydrus microstent insertions, with a minimum follow-up of 12 months. A learning curve analysis was performed by assessing hypotensive effect, adverse effects, and surgical procedure duration, with respect to consecutive case number. Success was defined with respect to various intraocular pressure (IOP) targets (21, 18, 15 mm Hg) and reduction in required antiglaucoma medications. Complete success was defined as achieving target IOP without antiglaucoma therapy. Results: No clinically significant adverse events or learning effects were identified, although surgical time reduced with consecutive case number. Mean follow-up was 16.8 months. At final follow-up the mean IOP for all eyes was reduced from 18.1 (±3.6) mm Hg [and a simulated untreated value of 25.9 (±5.2) mm Hg] to 15.3 (±2.2) mm Hg ( P =0.007; <0.0001) and the mean number of topical antiglaucoma medications was reduced from 1.96 (±0.96) to 0.04 (±0.20) ( P <0.0001). Complete success (IOP<21 mm Hg, no medications) was 96% at final follow-up. Complete success (IOP<18 mm Hg, no medications) was 80% at final follow-up, but only 32% with a target IOP of <15 mm Hg (no medications). Conclusions: No significant learning curve effects were observed for a trained surgeon with respect to MIGS microstent insertion performed at the time of cataract surgery. Adjunctive MIGS surgery was successful in lowering IOP to <18 mm Hg and reducing/abolishing the requirement for antiglaucoma medication in eyes with open-angle glaucoma, but less successful at achieving low IOP levels (<15 mm Hg).